A case of pleural neurofibroma: A rare pleural tumor (Indian Journal of Case Reports, 2018)
Neurofibromas (NFs) are benign tumors involving any nerve from the root level to the smallest branch. They may enlarge locally and cause a pressure effect on thoracic structures such as trachea, superior vena cava, and esophagus. Pulmonary and pleural involvement is very rarely seen. We have reported a case of a pleural effusion secondary to lymphatic obstruction due to remnant NF for which patient had undergone surgical resection in the past.